Anaesthetic implications in situs inversus totalis: a case report - Mansoor, Faraz; Qazalbash, Fatima Imran; Ahmad, Qazi Tauseef (Journal of the Pakistan Medical Association, 2024)
Situs inversus totalis (SIT) is a rare congenital condition which is characterised by the reversal of orientation of abdominal and thoracic organs where heart is on the right side of the thoracic cavity and liver on the left side, whereas stomach and spleen are on the right side in the abdomen. The reported prevalence of this anomaly is one in 5,000-20,000 live births. This case reports the anaesthetic management of situs inversus totalis in a 38-year-old male patient, with a history of poorly differentiated adenocarcinoma of the colon, who underwent laparoscopic intervention converted to open nodular excision with incisional hernia repair. The report analyses the anaesthetic implications and challenges associated with situs inversus totalis during surgery, including pre-operative evaluation, monitoring techniques and potential complications. Keywords: Situs inversus totalis, Anaesthesia, Kartagener’s syndrome, Dextrocardia.